PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID PADA MATERI HIDROLISIS GARAM - Tegar Budiman, - (2022)
Technological developments have reached the world of education. One of the technologies used is smartphones and the android system which is the most dominant compared to other systems. This study aims to develop an android-based application on salt hydrolysis material. The research method used is Development Research with the ADDIE development model. Feasibility in terms of material and media is carried out with a review by experts in terms of media and material. The limited trial was conducted using teacher and student response sheets to 3 educators and 5 students. Based on the location obtained from the media obtained that the simulation is used to test the pH solution available in the simulation, the image is used to clarify the part of the salt hydrolysis material. Based on the review and limited trials conducted, the multimedia developed is categorized as feasible in terms of media and material.